PENGARUH AUDITOR WORKLOAD, AUDITOR SWITCHING, AUDIT TENURE, DAN UKURAN KAP TERHADAP AUDIT REPORT LAG (ARL) - Fatikhasiwi Noor Aurumita; Herry Laksito (Diponegoro Journal of Accounting, 2025)
This research aims to obtain empirical evidence regarding the influence of Auditor Workload, Auditor Switching, Audit Tenure, and Public Accounting Firm Size on Audit Report Lag (ARL) of non-primary consumer sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The recurring phenomenon of delays in the submission of audited financial statements each year serves as the underlying issue of this research, which adopts agency theory as the theoretical framework to guide the analysis.The population of this study comprises non-primary consumer sector companies listed on the IDX from 2020 to 2024. This quantitative research employs purposive sampling to select the sample, resulting in 105 research samples for five consecutive years (2020–2024).The results of the multiple linear regression analysis indicate that auditor workload has a significant positive effect on audit report lag, while audit tenure has a significant negative effect. In contrast, auditor switching and public accounting firm size are found to have no significant effect on audit report lag.